2021
DOI: 10.3389/fonc.2021.632524
|View full text |Cite|
|
Sign up to set email alerts
|

TFEB Promotes Prostate Cancer Progression via Regulating ABCA2-Dependent Lysosomal Biogenesis

Abstract: Transcription factor EB (TFEB), a member of the MiT family, is dysregulated in different cancers and exerts specific biological functions within the tumor microenvironment. Downregulation of TFEB induces macrophage polarization in the TME and promotes tumor progression. However, the biological role and clinical significance of TFEB in prostate cancer (PCa) remain unknown. This study aimed to identify the role of TFEB in PCa and its potential clinical value. We explored TFEB expression in PCa using public datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Accumulating studies suggest that lysosomes are involved in tumorigenesis, drug resistance, and cancer therapy for various cancers, including prostate cancer [39], lung cancer [40], and BRCA [41]. Lysosomes manipulate growth factor signaling and provide nutrition in BRCA, therefore play a crucial role [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies suggest that lysosomes are involved in tumorigenesis, drug resistance, and cancer therapy for various cancers, including prostate cancer [39], lung cancer [40], and BRCA [41]. Lysosomes manipulate growth factor signaling and provide nutrition in BRCA, therefore play a crucial role [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of CQ and ifenprodil on spheroid formation were remarkable in GBM cells but not in nontransformed neural progenitor cells. These findings indicate that lysosomal activity or functions may be different between normal and malignant cells, and that cancer development and its malignant progression may be highly dependent on lysosomal activity 21 . For example, lysosomal activity is required to acquire energy essential for cancer cell proliferation 22 .…”
Section: Discussionmentioning
confidence: 98%
“…These findings indicate that lysosomal activity or functions may be different between normal and malignant cells, and that cancer development and its malignant progression may be highly dependent on lysosomal activity. 21 For example, lysosomal activity is required to acquire energy essential for cancer cell proliferation. 22 Uptake of extracellular materials mediated by phagocytosis, endocytosis, and micropinocytosis is needed to supply carbohydrates, lipids, and amino acids, which support cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, transcriptional regulation represents an additional important layer to control TFEB activity, with significant implications for cellular metabolism. Indeed, multiple studies correlate increased levels of TFEB with poor prognosis in several types of cancers, including glioblastoma [37], non-small lung cancer [38], breast carcinoma [39], and prostate cancer [40]. Recently, we demonstrated that sustained activation of TFEB is the main driver of renal tumorigenesis in a mouse model of BHD syndrome, which is caused by FLCN mutations, prompting research into strategies to counteract TFEB activation [9].…”
Section: Discussionmentioning
confidence: 99%